APPLICATION OF DIAGNOSTIC TEST INSTRUMENTS TO DETECT STUDENT'S MISCONCEPTIONS ON ACID-BASE MATERIALS - Iriani Bakti; Mutiara; Rusmansyah Muhammad; Cita Indira (Jurnal Pendidikan Kimia Undiksha, 2022)
Misconceptions are errors in a concept that must be identified early; it is essential so that it does not become the cause of errors in the next concept. This study aims to analyze the causes of misconceptions of class X students at SMK Negeri 2 Banjarmasin on acid-base material, which was measured using a four-tier diagnostic test instrument. This research method is descriptive quantitative-qualitative. They collect data using test techniques with four-tier diagnostic test instruments and non-tests through interviews. The results showed that 41.46% of students experienced misconceptions of acid-base theory sub-concepts by 46.73% (medium category), the nature of acid-base solutions had misconceptions of 29.44% (low category), acid-base indicators had misconceptions of 41, 43% (medium category), acid strength (pH) 44.86% (medium category) and the calculation of the pH of the solution concentration of 44.86% (medium category). The causes are misconceptions of wrong intuition, associative thinking, students' abilities, and learning interests. Keywords: misconception, four-tier ,acid base